EARLY CHRISTIANISATION OF JEWISH DAYS - Moolan, John (Asian Horizons, 2015)
Early Christians attempted to Christianise Jewish practices towards the economy of salvation fulfilled in Christ. In this regard, during the first three centuries, they did not even hesitate to uphold Christianised Jewish traditions in day-to-day life. The early Christian worshiping day was not the Jewish seventh day of Sabbath day, but Sunday, the first/eighth day of the week. Christians never preoccupied with any other day of the week due to Sunday’s special importance of resurrection with its eschatological dimension. The seven Jewish feasts were Christianised due to their relation to the paschal mysteries of Christ. The Jewish fast days of Wednesdays and Fridays in preparation for synagogue worshiping days, were related to Christ’s paschal foretelling and fulfilment of his suffering and death respectively on the same days. Martyrs’ courage in witnessing faith even at the risk of life made them real partakers of the paschal mysteries of Christ, and they were held in high esteem, as they were the real heroes of Christian faith.